First report of tinea corporis caused by Trichophyton quinckeanum in Iran and its antifungal susceptibility profile - Seyed Reza Aghili; Raheleh Alehashemi; Mahdi Abastabar; Farhad Niknejad; Iman Haghani; Fatemeh Livani; Amineh Kashiri; Javad Javidnia; Mohsen Nosratabadi (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Trichophyton quinckeanum, a known zoophilicdermatophyte responsible for favus form in rodents and camels, is occasionally reported to cause human infections.Case Report: This study aimed to report a case of tinea corporis caused by T. quinckeanum that experienced annular erythematous pruritic plaque with abundantpurulent secretions. In June 2021, a 15-year-old girl with an erythematous cup shape lesion on the right wrist bigger than 3 cm in diameter was examined for tinea corporis. Since March, 2016 her family has kept several camels at home. Direct examination of skin scraping and purulent exudates revealed branching septal hyaline hyphae and arthrospore. Morphological evaluation of the recovered isolate from the culture and sequencing of ITS1-5.8S rDNA-ITS2 region resulted in the identification of T. quinckeanum. Antifungal susceptibility testing showed that this isolate had low minimum inhibitory concentration (MIC) values for luliconazole,terbinafine, and tolnaftate, but high MICs to itraconazole, fluconazole, posaconazole, miconazole, isavuconazole, ketoconazole, clotrimazole, andgriseofulvin. However, the patient was successfully treated with oral terbinafine andtopical ketoconazole.Conclusion: It can be said that T. quinckeanum is often missed or misidentified due to its morphological similarity to T. mentagrophytes/T. interdigitale or other similar species. This dermatophyte species is first reported as the cause of tinea corporis in Iran. As expected, a few months after our study, T. quinckeanum was detected in other areas of Iran, in a few cases